2014
DOI: 10.1158/0008-5472.can-14-0305
|View full text |Cite
|
Sign up to set email alerts
|

BET Protein Inhibitor JQ1 Attenuates Myc-Amplified MCC Tumor Growth In Vivo

Abstract: Merkel cell carcinoma (MCC) is an aggressive neuroendocrine tumor of the skin currently with no cure. In this study, we have first demonstrated that c-Myc overexpression is common in MCC. By targeting c-Myc, bromodomain inhibitors have demonstrated antitumor efficacy in several preclinical human cancer models. Thus we interrogated the role of c-Myc inhibition in MCC with c-Myc amplification by employing the BET inhibitor JQ1. We have uncovered that c-Myc can be regulated by JQ1 in MCC cells with pathological c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 48 publications
(72 reference statements)
2
71
0
Order By: Relevance
“…Based on our previous findings, we have selected a total of 5 human MCC tumors in which c-Myc expression was examined by immunoblotting using an antibody against c-Myc. 18 Three tumors (tumors #11, #12 and #16) overexpressed c-Myc, whereas 2 tumors (tumor #10 and #15) had basal c-Myc expression. 18 We analyzed these 5 tumors for relative enrichment of H3K27Ac and BRD4 at the putative c-Myc super-enhancer region.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Based on our previous findings, we have selected a total of 5 human MCC tumors in which c-Myc expression was examined by immunoblotting using an antibody against c-Myc. 18 Three tumors (tumors #11, #12 and #16) overexpressed c-Myc, whereas 2 tumors (tumor #10 and #15) had basal c-Myc expression. 18 We analyzed these 5 tumors for relative enrichment of H3K27Ac and BRD4 at the putative c-Myc super-enhancer region.…”
Section: Resultsmentioning
confidence: 98%
“…13 Interestingly, we and another group have found that pathologic c-Myc amplification is common in MCC. 18,19 Moreover, we have also shown that JQ1 represses tumor growth in xenograft MCC mouse models, suggesting an epigenetic mechanism in regulating key oncogene expressions in MCC. 18 In this study, we sought to investigate the potential role of superenhancers in regulating c-Myc overexpression in MCC.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations